Climate change refugia for glaciers in Patagonia. (March 2021) - Manquehual-Cheuque, Francisco; Somos-Valenzuela, Marcelo
Abstract: The permanence of glaciers worldwide is uncertain due to increasing temperatures and decreasing precipitation. Glaciers are essential as strategic water reservoirs. They pose natural risks, constitute economic resources, and contribute to the rise in sea levels. Identifying places that remain relatively protected against these changes, and that could act as climate change refugia (CCR), is essential to understanding the impacts of climate change on glaciers. This study identified potential CCR for shrinking glaciers in Patagonia and the local characteristics that distinguished the response of glaciers to climate change. Using Maxent models, we calculated the probability that the current climate conditions, where glaciers are present, will be present in the future. To train the model, we used the Chilean glaciers inventory and the European Centre for Medium-Range Weather Forecasts Re-Analysis Interim datasets. For future scenarios, we used downscaled climate data for the representative concentration pathways 4.5 and 8.5. The resulting maps delivered the probability of areas that can act as CCR in different time periods and climate scenarios. Temperature and altitude are the most influential variables to identify CCR for glaciers in Patagonia, with the likelihood of CCR increasing along with increasing altitude. Glaciers at low altitudes, therefore, are vulnerable to dramatic changes, in particular if they are small. Three key processes in obtaining results should guide future studies: the sample of pseudoabsences differentiated by glaciological zone, comparison of models with different regularization coefficients, and the choice of the global circulation model. Improving such results in future models will increase understanding of shrinking glaciers in Patagonia and elsewhere around the world, which is an urgent issue under climate change.